Comparison of the Performance of SOEs Banks and Private Banks and its Influece to the Stock Prices - Husnul Insan; Yusman Syaukat; Imam Teguh Saptono (Indonesian Journal of Business and Entrepreneurship (IJBE), 2017)
Banking industry is one of the industries which show the presence of tight competition. The competition itself can be seen from the number of banks which operates in Indonesia in 2014, that is 119 banks. The aim of doing this research is to analyze the different financial performances between Significant effect on the level of 5% and Private banks, and also to analyze the variable influence of bank finance performances to the stock price. The analyzing method which will be used on this research is radar and regression analyzing graphic illustration techniques. The result of this research shows that financial performances of SEOs Banks is better than Private Banks according to the profitability, productivity, and growth potential aspect, while on the aspect of liquidity, private banks has a better performance than SOEs banks. In terms of solvability, both banks have the same financial performances. According to the regression analysis, it is known that the bank financial performance on CAS and NIM variable has a positive and significant influence to the stock prices, while on LDR, CRR, CAR, DRR, and ROA variables they have a negative and significant influence to the stock prices. This shows that the investors have made those variables as a benchmark in their investing policies and they tend to pursue the stocks from SOEs banks rather than private banks, because generally SOEs banks have a better financial performance than private banks.Keywords: regression analysis, bank, stock prices, financial performances, radar method